Relatability's role in formative assessment and feedback practices of young Black academics in an access university - Karabo Sitto-Kaunda; Ofentse Moroeng; Tebogo Makhubela (University of Johannesburg, 2023)
Transformation and diversification efforts in South African higher education system continue thirty years into democracy. Access universities play a crucial role in attracting students from previously excluded groups to higher education, specifically Black learners from poor schools with the least resources. Black lecturers in access universities, through shared cultural identities and backgrounds, carry an unspoken responsibility, beyond academic duties, to develop inclusive assessment and feedback practices. This unspoken responsibility must be carried out without compromising academic curriculum requirements and became acutely important during the COVID-19 lockdown period. Through transdisciplinary pragmatism in pedagogical practice, relatability ensures that students engage in meaning-making through participation in the development of solutions that address hyper-localised problems, thus contextualising science in real-world contexts. This study evaluates the role of relatability in the development of inclusive, transdisciplinary, and pragmatic formative assessment and feedback practices for student success in higher education. It does this by comparing the practices and experiences of young, Black lecturers in an access university. Our formative assessment and feedback methodologies and analysis of our teaching portfolios are presented to demonstrate how our personal student experiences have shaped more inclusive practices. In the discussion, we highlight the influence of unspoken responsibilities on Black lecturers to develop student outcomes beyond academic success through assessment and feedback. We seek to highlight how relatability can be leveraged to improve formative assessment and feedback practices towards strengthening inclusive teaching and learning for students' academic success.